Management of the training process in cross-country orienteering on the basis of typical model characteristics of competitive activity and special preparation of the necessary norms - Voronov Yu.S.; Obvintsev A.A.; Gurskiy A.V.; Efremenkov K.N. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to experimental justification of the methodical management of the training process of young orienteering athletes based on the use of typical model characteristics of competitive activity and special preparation of proper norms. Methods and structure of the study. Scientific and methodical literature, reports and planning documents were analyzed in the scientific work. Also, a survey was conducted, in which qualified sportsmen (MS-CMS), specializing in cross-country orienteering, and coaches of various categories took part. Results and conclusions. Developed and theoretically justified model characteristics for athletes 13-18 years old, specializing in running orienteering. The implementation of the obtained model characteristics in the activities of sports schools allowed to significantly increase the effectiveness of the formation of technical and tactical mastery of orienteering athletes at various stages of the long-term training process.